CONTROLLING FACTORS TO THE DISTRIBUTION OF SALINITY OF POREWATER IN QUATERNARY MARINE SEDIMENTS IN NAM DINH AREA - Hoan, Hoang Van; Nhan, Pham Quy; Larsen, Flemming; Chuyen, Nguyen The (Vietnam Journal of Earth Sciences, 2014)
This paper presents the results of studies and analysis, assessment the controlling factors to the distribution of salinity (mainly NaCl) in the Quaternary marine sedimentary in Nam Dinh area by using a combination of different methods such as boreholes logging, undisturbed sediment sampling, pore water squeezing, analysis of chemical and stable isotope compositions of pore water. Based on the correlation between concentration of Cl-, Na+ ions and NaCl versus electrical conductivity of marine sediment at different depth according to geophysical borehole results determine the distribution of concentration of salinity (NaCl) of pore water at different depths. In addition, results from the analysis of stable isotopes δ18O and δ2H of porewater in the marine sedimentary layer show the mixing of marine water and meteoritic water in the sediments. Distribution of NaCl of marine sediments is due to difference in density and molecular diffusion. References Charles D. Shackelford, David E. Daniel, 1990. Diffusion in Saturated soil. Journal of Geotechnical Engineering 117, 467 - 484. Crooks, V. E. and Quigley, R. M., 1984. Saline leachate migration through clay: A comparative laboratory and field investigation. Can. Geotech. J., 21(2), 349 - 362. Đoàn Văn Cánh, Lê Thị Lài, Hoàng Văn Hưng, Nguyễn Đức Rỡi, Nguyễn Văn Nghĩa, 2005. Groundwater Resource Of Nam Định Province, J. of Geology, B/25, Hà Nội. Frank Wagner, Dang Tran Trung, Hoang Dai Phuc, Falk Lindenmaier, 2011. Assessment of Groundwater Resources in Nam Dinh Province. Final Technical Report of improvement of Groundwater Protection in Vietnam, Ha Noi. Hoàng Văn Hoan, Flemming Larsen, 2007. Phương pháp xác định độ lỗ hổng hiệu dụng, hệ số thấm của tầng chứa nước và TDS của nước bằng phương pháp địa vật lý lỗ khoan, lấy ví dụ vùng đồng bằng sông Hồng. TC KHKT Mỏ - Địa chất, 20/10-2007. Hà Nội, 101-107. Hoan V. Hoang, Nhan Q. Pham, Flemming Larsen, Long V. Tran, Frank Wagner And Anders V. Christiansen, 2011. Processes Controlling High Saline Groundwater in the Nam Dinh Province, Vietnam. 2nd Asia-Pacific Coastal Aquifer Management Meeting October 18-21, 2011, Jeju Island, Korea. Hoàng Văn Hoan, Phạm Quý Nhân, Flemming Larsen, Trần Vũ Long, Nguyễn Thế Chuyên, Trần Thị Lựu, 2012. Ảnh hưởng của quá trình khuếch tán tới sự phân bố độ mặn của nước lỗ rỗng trong lớp trầm tích biển tuổi Đệ tứ khu vực Nam Định. Báo cáo hội nghị khoa học lần thứ 20, ĐH Mỏ - Địa chất. Hà Nội. Nguyễn Kim Ngọc, Kiều Vân Anh, Nguyễn Thị Hạ, Hoàng Văn Hoan, Đỗ Tiến Hùng, Hoàng Văn Hưng, Nguyễn Văn Lâm, Phạm Quý Nhân, Nguyễn Thị Thanh Thủy, 2005. Thủy Địa Hóa học. Nhà xuất bản Giao thông vận tải, Hà Nội, 315tr. Kooi H., Groen J., Leijnse A., 2000. Modes of seawater intrusion during trangressions, Water resources research, Vol. 36, No. 12, phương pháp 3581-3589. Rowe, R. K., Caers, C. J., and Barone, F., 1988. Laboratory determination of diffusion and distribution coefficients of contanminants using undisturbed clayey soil. Can. Geotech. J., 25, 108-118. Schincariol RA, Schwartz FW, Mendoza CA., 1997. Instabilities in variable density flows: stability and sensitivity analyses for homogeneous and heterogeneous media. Water Resour Res; 33(1), 31-41. Simmons CT, Fenstemaker TR, Sharp JM., 2001. Variable-density groundwater flow and solute transport in heterogeneous media approaches resolutions and future challenges. J Contam Hydrol; 52(1-4), 245-75. 148. Tanabe, S., Hori, K., Saito, Y., Haruyama, S., Vu, V.P., Kitamura, A., 2003a. Song Hong (Red River) delta evolution related to millen-nium-scale Holocene sea-level changes. Quaternary Science Reviews 22, 2345-2361. Tanabe, S., Hori, K., Saito, Y., Haruyama, S., Doanh, L.Q., Sato, Y., Hiraide, S., 2003b. Sedimentary facies and radiocarbon dates of the Nam Dinh-1 core from the Song Hong (Red River) delta. Viet-nam. Journal of Asian Earth Science 21, 503-513. Tanabe, S., Hori, K., Saito, Quang Lan Vu, Till J. J. Hanebuth, Quang Lan Ngo, Akihisa Kitamura, 2006. Holocene evolution of Song Hong (Red River) delta system, north Vietnam. Sedimentary Geology 187, 29-61. Weixing Guo and Christian D. Langevin, 2002. User’s Guide to SEAWAT: A computer program for simulation of three-dimensional variable-density groundwater flow, USGS, Florida, USA.